Assistência social e práticas institucionais no atendimento a andarilhos de estrada - Nascimento, Eurípedes Costa Do [UNESP]; Justo, José Sterza [UNESP] (Programa de Pós-Graduação em Psicologia, Pontifícia Universidade Católica de Campinas, 2014)
In a contemporary context, highway wanderers can be seen as one of the most radical expressions of a break from socially fixed niches, travelling on foot along Brazil's highways and, when emergency needs must be met, seeking support from institutional care services. This study seeks to identify which institutional practices are provided to highway wanderers by social services, based on reports by managers of such services. The research was carried out at four institutional care services in the state of São Paulo , through the application of semi-structured interviews. The results show that the institutional practices provided to highway wanderers by social services include disciplinary techniques involving power and knowledge applied by means of procedures and rules that impose obedience along with an inspection of their bodies and a search of their belongings. In conclusion, the social service practices that are provided to highway wanderers become strategic tools of power and control over the bodies and itinerant lives, seeking to subsume such a subjectifying process within disciplinary techniques.

Os andarilhos de estrada se configuram na contemporaneidade como uma das expressões mais radicais de rompimento com os nichos de fixação social, caminhando a pé pelas rodovias do país e, quando de suas necessidades emergenciais, buscando apoio nas instituições assistenciais. Este artigo visa identificar quais práticas institucionais o serviço social realiza com os andarilhos, segundo os relatos de seus dirigentes. A pesquisa foi realizada em quatro instituições assistenciais no estado de São Paulo, por meio de um roteiro de entrevista semiestruturada. Os resultados indicaram que as práticas institucionais do serviço social em relação aos andarilhos envolvem tecnologias disciplinares de poder e saber, mediante procedimentos e regras que impõem a obediência e a vistoria do seu corpo e pertences. É possível concluir que as práticas do serviço social no atendimento aos andarilhos convertem-se em ferramentas estratégicas de poder no controle de corpos e vidas errantes, visando subordinar tal processo de subjetivação às tecnologias disciplinares.
Social services and institutional practices provided to highway wanderers
Keywords: Análise institucional; Andarilhos; Serviço de assistência social; Institutional analysis; Wanderers; Social services